Teaching English Vocabulary Using Anagrams to the Eighth Grade Students of SMP Negeri 5 Palembang - Saputri, Kurnia (Yayasan Corolla Education Centre, 2021)
This research was focused on strategy of Teaching English Vocabulary Using Anagrams to the Eighth Grade Students of SMP Negeri 5 Palembang. The formulation of the problem in this study was ”is it effective to teach English vocabulary by using anagrams to the eighth grade students of SMP Negeri 5 palembang?”. Meanwhile, the objective of this study was to find out whether or not it was effective to teach english vocabulary by using anagrams to the eighth grade students of SMP Negeri 5 palembang?. The population was all of the eighth grade students SMP Negeri 5 palembang. With the total number 30 students for sample. The sample of this study was taken from the population by using non random sampling. The true experimetal method was used in this study. The data obtained were analyzed by using SPSS 16.0 (Statistical Package for Social Science). Based on sample t – test, it was found that the t- obtained was 10,871, which was 0.05 of the level significance with the degree of freedom (df) was 29 with the critical value of the t- table 0.306. because t-obtained 10,871 was higher than t-table 0,306. It meant that there was significant difference between the eighth grade student of SMP Negeri 5 Palembang who were using anagrams and those were not. It also indicated that anagrams could improved the students vocabulary skill for the eighth grade students of SMP Negeri 5 Palembang.